Sistem Baterai Cell Balancing Pasif Menggunakan Kontrol Logika Fuzzy Tipe Mamdani untuk Baterai Pack Lithium - Moh Rifqi Faqih; Novie Ayub Windarko; Endro Wahjono (J-Innovation, 2021)
Lithium-ion batteries have been widely used in energy storage for electric vehicle and hybrid vehicle applications. After several cycles of charging and discharging, there is one cell whose performance and capacity decreases, causing the performance and capacity of the battery pack to decrease so that it cannot work optimally. So it is necessary to design a cell voltage balancing system to minimize cell voltage imbalance in the charging process. Passive balancing is widely implemented because of its simplicity, reliability, and relatively low cost. The balancing process must be carried out as quickly as possible as the battery is charging, so a PWM ignition technique using mamdani fuzzy is needed to discharge an unbalanced battery cell. The result are compared with no balancing system, fixed balancing 50% duty cycle system, and sugeno fuzzy logic balancing system. From the simulation result, using mamdani fuzzy the final delta voltage value is 0.0344 volt, energy charged is 58.18 Wh and the final State of Charge is 74%. When compared with other balancing method, it shows that using mamdani fuzzy logic method is more optimal because the final of delta voltage value is very small and the battery capacity charged is larger than other method.